Association of imbalance between job workload and functional ability with return to work in ARDS survivors. Issue 2 (29th April 2021) - Su, Han; Hopkins, Ramona O; Kamdar, Biren B; May, Susanne; Dinglas, Victor D; Johnson, Kurt L; Hosey, Megan; Hough, Catherine L; Needham, Dale M; Thompson, Hilaire J
Abstract : Background: Inability to return to work (RTW) is common after acute respiratory distress syndrome (ARDS). Mismatch in an individual's job workload and his or her functional ability, termed work ability imbalance, is negatively associated with RTW, but has not been evaluated in ARDS survivors. Object: We examine associations between work ability imbalance at 6 months and RTW at 6 months and 12 months, as well as the ability to sustain employment in ARDS survivors. Methods: Previously employed participants from the ARDS Network Long-Term Outcomes Study (N=341) were evaluated. Pre-ARDS workload was determined based on the US Occupational Information Network classification. Post-ARDS functional ability was assessed using self-reported 36-Item Short Form Health Survey (SF-36) physical functioning, social functioning and mental health subscales, and Mini-Mental State Examination. ARDS survivors were categorised into four work ability imbalance categories: none, psychosocial, physical, and both psychosocial and physical. Results: Almost 90% of ARDS survivors had a physical and/or psychosocial work ability imbalance at both 6-month and 12-month follow-up. Compared with survivors with no imbalance at 6 months, those with both physical and psychosocial imbalance had lower odds of RTW (6 months: OR=0.33, 95% CI=0.13 to 0.82; 12 months: OR=0.22, 95% CI=0.07 to 0.65). Thirty-eight (19%) of those who ever RTW were subsequently jobless at 12 months. Conclusion: Interventions aimed at rebalancing ARDS survivors' work ability by addressing physical and psychosocial aspects of their functional ability and workload should be explored as part of efforts to improve RTW, maintain employment and reduce the financial impact of joblessness.